CONCEPTUAL APPROACH TO THE DIMENSIONS OF THE SOCIAL INTELLIGENCE. : Nucleus of endogenous development in Venezuela (Agroindustria, Sociedad y Ambiente, 2016)
Social Intelligence, as an endogenous factor allows the development from inside - out, first in the person, then in the society and later in the nation. In this sense the present descriptive field research made an assessment of the conceptual approach to the Social Dimensions of Intelligence (IS) having the members of Endogenous Development Dyer, located in the Lara- Venezuela. For this purpose was applied an instrument under the linker scale with twenty items to a population consisting of 59 persons, who were active representatives of the nuclei of development. The instrument applied passed through a process of expert judgment validity and reliability test Cronbach's alpha yielded a value of 0.81, ensuring that the instrument was reliable. It should be noted that for processing data was used descriptive statistics by SPSS, version 20.0, based on graphs made in Excel for Windows. The results show that the theoretical raise the endogenous development is determined by factors inherent to the Social Intelligence (IS), such as empathy and interpersonal relations. Also in the context of endogenous nuclei studied indicate that one of the dimensions of the IS as Tolerance, showed a trend of response showing that most of the time, social actors of this core, have a tolerance level low.
Keywords: Social Intelligence, Development, Endogenous Core.